The Parthica of Pseudo-Appian - Mallan, C (Franz Steiner Verlag, 2017)
The Parthica found in the manuscripts of Appian's Roman History has received little attention since the work was shown to be a forgery by Schweighäuser in the late 18th Century. Since then it has been assumed that the work is of Byzantine provenance, and it has been omitted from subsequent scholarly editions of Appian. This article presents a reconsideration of the Parthica, its date, and the possible intentions of its pseudonymous author. It is argued that the work, whether or not an example of deliberate literary imposture, may in fact be of far greater antiquity than what is generally thought.